2014
DOI: 10.1007/s10853-014-8435-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful intercalation of DNA into CTAB-modified clay minerals for gene protection

Abstract: Montmorillonite (MMT) and rectorite (REC) are clay minerals that consist of hydrated aluminum silicate with Si-O tetrahedrons on the bottom of the layer, Al-O(OH) 2 octahedrons on the top, and various exchangeable ions such as Na ? and Ca 2? in interlayer. However, the driving force for intercalation of double-stranded DNA is not sufficient to open up the gallery of MMT and REC and allows the intercalation to occur. Furthermore, the external surface of MMT and REC is hydrophilic rather than organophilic. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…On the other hand, the previous transport, magnetization and specific heat measurements showed that there is no clear indication of strong electron correlations in the electronic properties of Cu pyrites. [11] It is chalcogen š‘ character rather than š‘‘ characteristic of Cu that dominates at the Fermi level, [11,12] which is in remarkable contrast to other 3š‘‘ transition metal pyrites.…”
mentioning
confidence: 99%
“…On the other hand, the previous transport, magnetization and specific heat measurements showed that there is no clear indication of strong electron correlations in the electronic properties of Cu pyrites. [11] It is chalcogen š‘ character rather than š‘‘ characteristic of Cu that dominates at the Fermi level, [11,12] which is in remarkable contrast to other 3š‘‘ transition metal pyrites.…”
mentioning
confidence: 99%
“…Investigations of 16 on the effect of pH on the adsorption of DNA to clay minerals have shown that adsorption capacity decreased at higher pH [24,36]. Recently, Hou et al [47] demonstrated that clay minerals modified with CTAB have a greater capacity for DNA adsorption and intercalation of DNA into the clay galleries. This mechanism may contribute to the overall low performance of CTAB-based protocols on clay soils.…”
Section: Discussionmentioning
confidence: 99%
“…discussed the role of clay minerals and layered double hydroxides in various biological applications (Choy et al ., 2007). Intercalation of DNA into CTAB-modified clay minerals for gene protection concluded that CTAB-clay/DNA hybrids are potential materials for the storage of genetic information (Hou et al ., 2014). Brack (2013) and Ponnamperuma et al .…”
Section: Introductionmentioning
confidence: 99%